2017
DOI: 10.1051/matecconf/201712005005
|View full text |Cite
|
Sign up to set email alerts
|

Date seed derived biochar for Ni(II) removal from aqueous solutions

Abstract: Abstract. The purpose of this study was to investigate the adsorption characteristic of biochars derived from date seed for Ni 2+ ions removal from aqueous solutions. Two biochars were prepared by slow pyrolysis of date seed for 3 h at 450 °C (DSB450) and 550 °C (DSB550). The adsorption of Ni 2+ was carried out by batch experiments at room temperature. The effects of pyrolysis temperature, contact time, initial metal concentration, and solution pH were investigated. The results showed that biochar prepared at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Similar observations were reported by other researchers [3,43]. Furthermore, DSB550-3 biochar exhibits a high ash content (12.67 %) with CEC of 1.897 meq L -1 [19] suggesting that the biochar may exhibit a high tendency to adsorb Cu 2+ and Ni 2+ by releasing other cations such as K + , Ca 2 + , and Mg 2 + .…”
Section: Ion Exchangesupporting
confidence: 89%
See 1 more Smart Citation
“…Similar observations were reported by other researchers [3,43]. Furthermore, DSB550-3 biochar exhibits a high ash content (12.67 %) with CEC of 1.897 meq L -1 [19] suggesting that the biochar may exhibit a high tendency to adsorb Cu 2+ and Ni 2+ by releasing other cations such as K + , Ca 2 + , and Mg 2 + .…”
Section: Ion Exchangesupporting
confidence: 89%
“…In our previous studies, biochar derived from date seed biomass showed remarkable, adsorption capacities for MB removal from aqueous solution [18]; our preliminary study [19] also suggested a good potential for Ni adsorption. Therefore, date seed derived biochar may be an efficient low-cost adsorbent for heavy metals and dyes.…”
Section: Accepted Manuscriptmentioning
confidence: 58%
“…These results join previous reports (Ali et al, 2020b;Mahdi, Qiming & Hanandeh, 2018;Pedrero et al, 2010;Rageh, 2014) in establishing the capacity of biochar to alleviate the content of heavy metals from contaminated soils. For examples, rice straw biochar has proven its efficiency in alleviating Ni 2+ toxicity and remediating Ni 2+ -contaminated soils by decreasing the Ni 2+ mobility and leachability in the soil (Ali et al, 2020a;Ali et al, 2020b), also date seed derived biochar has shown significant capacity to adsorb copper (Cu 2+ ) and Ni 2+ ions from aqueous solution, and the ions removal depended on the pyrolysis temperature and time used in biochar preparation and the biochar dose (Mahdi, El Hanandeh & Yu, 2017a;Mahdi, El Hanandeh & Yu, 2017b), moreover the biochar produced from wood waste revealed significant potential of Cu 2+ adsorption from the soil as well the Cu 2+ adsorption quantity increased with the increase of the biochar doses and pH value (Tomczyk, Boguta & Sokołowska, 2019). In other studies, it was previously reported that the adsorption capacity of biochar is related to its pH and cation exchange capacity (CEC) values.…”
Section: Mitigation Of Ni T2+ Contamination In the Soil By Biocharmentioning
confidence: 99%